Isolated cryptococcal osteomyelitis as a differential diagnosis of hallux valgus - Toumie, Sahar; Matucci, Tommaso; Fabiani, Silvia; Falcone, Marco; Leonildi, Alessandro; Parchi, Domenico Paolo (Acta Biomedica Atenei Parmensis, 2024)
Cryptococcus neoformans is a ubiquitous encapsulated yeast that causes infection as an opportunistic agent primarily in immunocompromised patients, and more rarely, in immunocompetent subjects. Cryptococcal bone involvement can occur in the context of a disseminated infection or as single localization due to, for example, direct inoculation through traumatic injuries or during surgery and minor procedures. Cryptococcosis must be, therefore, included in the differential diagnosis of osteolyic lesions. Bone biopsy should be performed to confirm the diagnosis of cryptococcal infection and to initiate an early course of therapy. Hereby, we present a case of an extrapulmonary isolated cryptococcal osteomyelitis in a female affected with multiple sclerosis (MS), firstly evaluated for hallux valgus, and later diagnosed with a cryptococcal infection by performing a bone biopsy. As there are no codified guidelines on treatment in cryptococcal osteomyelitis we have chosen a combined approach with medical and surgical management with success at 1 year follow-up.